Plan de negocios para la exportación de camarón hacia el mercado de Dubái desde la empresa Procamaronex de Guayaquil en el 2022. - Guaman Guayas, Cristhian Alberto; Ordoñez Ordoñez, Josselyn Daniela (Universidad Técnica de Machala, 2022)
Considering the current dynamics of growing shrimp exports and the considerable commercial opening and support that the Government is carrying out in conjunction with the private sector, this research proposes the development of a strategic plan for the export of Ecuadorian shrimp to Dubai. Especially in a context where shrimp is the product that leads non-oil exports in the country and that, in addition, for the first time, in 2021 national aquaculture production catapulted Ecuador as the main exporter of shrimp in the world. In addition, the diversification of the client portfolio and exploration of new destinations for the country's flagship product is considered relevant, due to the high concentration of exports in the Chinese market. The main objective of this research is to develop a strategic export plan for the company Procamaronex from Guayaquil to the Dubai market in 2022, thus determining the feasibility of the project. Through a mixed approach, the research developed qualitative aspects that include the CANVAS model, VRIO analysis and SWOT matrix, it also presented quantitative aspects by the method of determining the TCAG of the supply and demand of Ecuadorian shrimp to Dubai, to find the opportunity to market. This research also considered the relevance of cultural aspects to carry out negotiations in Middle Eastern markets. In addition to this, a financial analysis of the investment project is included to develop the strategic plan. The results reveal that there is a market opportunity in Dubai for Ecuadorian shrimp given that the CAGR of the demand is greater than the CAGR of the supply, and that the proposal for the PROCAMARONEX company is feasible and profitable with an IRR of 72%. and an investment payback period of 1.41.
Considerando la dinámica actual de crecimiento de las exportaciones de camarón y la notable apertura comercial y apoyo que está realizando el Gobierno en conjunto con la empresa privada en incentivar exportaciones, esta investigación propone el desarrollo de un plan estratégico de exportación del camarón ecuatoriano. Especialmente ante un contexto donde el camarón es el producto que lidera las exportaciones no petroleras en el país y que, además, por primera vez, en el año 2021 la producción acuícola nacional catapultó al Ecuador como el principal exportador de camarón en el mundo. En adición, se considera relevante la diversificación de cartera de clientes y exploración de nuevos destinos para el producto estrella del país, debido a la alta concentración de las exportaciones en el mercado chino. El principal objetivo de esta investigación es desarrollar un plan estratégico de exportación para la empresa Procamaronex de Guayaquil con destino al mercado Dubaití en el año 2022, determinando así la factibilidad del proyecto. Mediante un enfoque mixto, la investigación se desarrolló aspectos cualitativos que incluyen el modelo CANVAS, análisis VRIO y matriz FODA, también presentó aspectos cuantitativos por el método de determinación de la TCAG de la oferta y demanda de camarón ecuatoriano hacia Dubái, para encontrar la oportunidad de mercado. En esta investigación también se consideró la relevancia de aspectos culturales para realizar negociaciones en mercados de Medio Oriente. Sumado a esto, se incluye un análisis financiero del proyecto de inversión para desarrollar el plan estratégico. Los resultados revelan que existe una oportunidad de mercado en Dubái para el camarón ecuatoriano dado que la TCAG de la demanda es mayor a la TCAG de la oferta, y que además la propuesta para la empresa PROCAMARONEX es factible y rentable con una TIR de 72% y un periodo de retorno de inversión de 1.41.
Keywords: CAMARON; ECUADOR; EXPORTACION